Telaah Feminisme Dalam Puisi “Impressions From An Office” Karya N. Josefowitz - amin khudlori (Universitas Aki, 2016)
Poetry is a unique way to express someone‟s feelings. Sometimes the poetry is the author‟s experience. In writing this research the writer uses two methods, namely method of collecting data and method of approach. The method of collecting data which the writer used is the library research method, in which various sources are collected and also used to support his discussion. In approaching the poetry, the writer uses the objective or the structural approach method and feminism approach method to get deeper understanding of the poem. There are some objectives which the writer wants to achieve in conducting this research. Some of the objectives are to get deeper understaanding on feminism found in N. Josefowitz‟ poem Impressions from an Office, to find out the effects of people social condition and the effects of feminism movement which is growing in America, and to find out the implicit meanings of N. Josefowitz‟ poem mentioned above. Feminism in one hand is a kind of social movement that aims at gender equal relationship. On the other hand, it is a kind of literary approach. The principle of feminism as literary approach is based on how literary work reflects gender aspects. A poetry written by N. Josefowitz as a kind of literature will be used in this paper as an object of study. By analyzing that poetry, we will understand how feminism as a social movement affects literary approach. Keywords: feminism, gender, equality, social, poetry.